2021
DOI: 10.30766/2072-9081.2021.22.2.212-222
|View full text |Cite
|
Sign up to set email alerts
|

Search for the parent material of spring soft wheat resistant to septoria tritici blotch and analysis of the trait inheritance

Abstract: In 2017-2020 in the conditions of Kirov region there were studied 143 varieties, 115 perspective lines and 28 hybrids of the first generation of spring soft wheat according to the degree of resistance to septoria tritici blotch against the background of the natural development of infection. It has been established that development of the disease significantly increased with a decrease in air temperature during the «seedling-tillering» phase (r = -0.83…-0.96) and an increase in the amount of precipitation durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…It was shown that drip liquid water is needed to release asexual spores from pycnids; therefore, precipitation of at least 10 mm, continuous three-day 1 mm rainfall at a moderate temperature, high humidity (98%), or regular dewfall was necessary to trigger wheat infection. Spread of propagules in leaf canopy is accelerated if they are splashed with raindrops [46]. Examples of wheat crops in the Moscow and Kirov regions showed that in rainy weather leaf lesion occurred during the tillering stem elongation period and could lead to plant death [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that drip liquid water is needed to release asexual spores from pycnids; therefore, precipitation of at least 10 mm, continuous three-day 1 mm rainfall at a moderate temperature, high humidity (98%), or regular dewfall was necessary to trigger wheat infection. Spread of propagules in leaf canopy is accelerated if they are splashed with raindrops [46]. Examples of wheat crops in the Moscow and Kirov regions showed that in rainy weather leaf lesion occurred during the tillering stem elongation period and could lead to plant death [8].…”
Section: Discussionmentioning
confidence: 99%
“…Examples of wheat crops in the Moscow and Kirov regions showed that in rainy weather leaf lesion occurred during the tillering stem elongation period and could lead to plant death [8]. Release of spores from pycnidias did not occur without liquid water and at low humidity, and led to the suppression of the disease [13,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Отечественные фитопатологи и селекционеры ведут постоянный поиск сортов и линий с высокими иммунологическими и другими селекционно ценными свойствами (Pakholkova et al, 2022;Sibikeev et al, 2022;Baranova et al, 2023). В производстве должны преимущественно возделываться сорта пшеницы с долговременной неспецифической устойчивостью (Kharina, Sheshegova, 2021).…”
Section: материалы и методыunclassified